Bone stable isotope data of the Late Roman population (4th–7th centuries CE) from Mondragones (Granada): A dietary reconstruction in a Roman villa context of south-eastern Spain - Fernández-Martínez, Paula (2022)
The aim of this study is to examine the diet, using bone stable isotope analysis (δ13C and δ15N), of a Late Roman population (4th–7th centuries CE) from the Roman villa of Mondragones (Granada, Spain). This archaeological site presents an exceptionally high number (n = 121) of well-preserved skeletal remains (adults and non-adults), giving the opportunity to study for the first time the nutritional and health conditions of a Late Roman population by the analysis of stable isotopes and pathologies in the context of the south-eastern Iberian Peninsula. Stable isotopes ratios of carbon (δ13C) and nitrogen (δ15N) were analysed in 46 individuals (21 adults and 25 non-adults) as well as in 7 faunal samples (2 cows/ox, 2 goats/sheep, and 3 large mammals). Frequencies of cariogenic lesions, dental calculus, dental enamel hypoplasia, porotic hyperostosis, and cribra orbitalia were also explored. The anthropological study revealed a high presence of dental caries and calculus in adults, which are related to a diet rich in starch and carbohydrates, and non-specific stress markers in non-adults, probably pointing to the weaning process or childhood diseases. Collagen isotope ratios suggested that the population of Mondragones had a diet rich in C3 plants, with some meat intake from terrestrial herbivores. There were significant differences between non-adults and adults, but no differences were detected by sex. The youngest non-adults (aged 1 year ± 4 months) showed the δ15N mean value almost 4‰ above the adult female one, which could reflect the breastfeeding period.